No gender difference in willingness to compete when competing against self - Coren L. Apicella; Elif E. Demiral; Johanna Mollerstrom (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
We report on two experiments investigating whether there is a gender difference in thewillingness to compete against oneself (self-competition), similar to what is found whencompeting against others (other-competition). In one laboratory and one online marketexperiment, involving a total of 1,200 participants, we replicate the gender-gap inwillingness to other-compete but find no evidence of a gender difference in the willingnessto self-compete. We explore the roles of risk and confidence and suggest that these factorscan account for the different findings. Finally, we document that self-competition does noworse than other-competition in terms of performance boosting.
Keywords: C90; C91; J16; J71; 330; gender; competition; discrimination; experiment